A SYSTEM OF INDICATORS FOR INNOVATIVE DEVELOPMENT IN INDUSTRIAL ENTERPRISES (World Economics and Finance Bulletin, 2026)
This article provides a scientifically grounded system of indicators designed to assess and monitor innovative development in industrial enterprises. The study examines the need to systematise innovative development metrics and analyses the advantages and limitations of existing methodological approaches. In particular, the Oslo Manual (OECD), the Frascati Manual, and the Global Innovation Index (GII) methodologies are reviewed in the context of their applicability to Uzbek industrial enterprises. The article presents a structured classification of input indicators (innovation-oriented investment, R&D expenditure, human capital capacity) and output indicators (share of new products, patent activity, export competitiveness), and proposes an integrated assessment methodology encompassing all dimensions of innovation activity
Keywords: Innovative development; indicator system; industrial enterprise